PENGARUH KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSAEFEK INDONESIA (BEI) - RAHMAWATI, ANITA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
The value of the company reflects investor?s perception on the success of a company that are often associated with stock prices. High stock price influences the value of the company's and will impress the market of company's current and future performances. The purpose of this study is to determine the influence of managerial ownership and the size of the company to the value of the company in the manufacturing industry listed on the Indonesia Stock Exchange (BEI) in the period of 2011-2012. Population consists of manufacturing industry with managerial ownership whose shares are listed and actively traded on the Indonesia Stock Exchange (BEI) in the period 2011-2012. The data in this research is secondary data obtained from the Indonesia Stock Exchange. Sampling method is purposive sampling. The number of samples taken based on the criteria is 20 companies. Data analysis method is multiple linear regression analysis. The test results show that managerial ownership and firm size simultaneously have significant influence on the value of manufacturing companies in the Indonesia Stock Exchange. Partially, managerial ownership and the size of the company significantly have negative influence on the value of companies in the manufacturing industry in the Indonesia Stock Exchange.